2006
DOI: 10.1089/jpm.2006.9.1164
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Caregivers for the Death of a Loved One: A Theoretical Framework and Suggestions for Future Research

Abstract: Caring for a terminally ill loved one and the death of that person are two of the most stressful human experiences. Recent research suggests that a substantial number of caregivers are unprepared for the death and that these caregivers may be at greater risk of psychological distress. The literature on preparedness and mental health, however, is in its infancy. The purpose of this paper, therefore, is to summarize the literature in order to stimulate discussion and research on preparedness. It is our view that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
181
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(186 citation statements)
references
References 53 publications
3
181
0
1
Order By: Relevance
“…These include older age, [127][128][129] women (rather than men), [127][128][129] spouses, 129 losing a younger family member, 128 past grief experience, 127,130 close bonds to the deceased, 130 lack of bereavement coping self-efficacy, 131 lower religiousness, 132 lack of social support, 9,41 greater number of adverse life events, 130 lack of self-efficacy, 130,131 shorter time between diagnosis and death, 36 greater severity of the patient's illness, 130 perceived caregiving burden, 104,129 and being unprepared for the relative's death. 133 Again, other than studies of psychological distress at the bereavement phase, studies examining aspects of the QOL of cancer caregivers are sparse. One study with recently bereaved older individuals indicated that healthy behaviors, such as consistent exercise, monitoring caloric intake, and proper amount of sleep at 6-and 11-months postloss, were related to better QOL at 19-months postloss.…”
Section: Family Caregivers' Qol At the Bereavement Phasementioning
confidence: 99%
“…These include older age, [127][128][129] women (rather than men), [127][128][129] spouses, 129 losing a younger family member, 128 past grief experience, 127,130 close bonds to the deceased, 130 lack of bereavement coping self-efficacy, 131 lower religiousness, 132 lack of social support, 9,41 greater number of adverse life events, 130 lack of self-efficacy, 130,131 shorter time between diagnosis and death, 36 greater severity of the patient's illness, 130 perceived caregiving burden, 104,129 and being unprepared for the relative's death. 133 Again, other than studies of psychological distress at the bereavement phase, studies examining aspects of the QOL of cancer caregivers are sparse. One study with recently bereaved older individuals indicated that healthy behaviors, such as consistent exercise, monitoring caloric intake, and proper amount of sleep at 6-and 11-months postloss, were related to better QOL at 19-months postloss.…”
Section: Family Caregivers' Qol At the Bereavement Phasementioning
confidence: 99%
“…Therefore, as health professionals, we have to be vigilant in order to distinguish the period necessary for emotional integration from the inability for parents to integrate the child's death. In the same way, literature regarding preparation for the death of a loved one emphasizes a frequent difference between cognitive comprehension of the fatal prognosis (comparable to intellectual awareness) and the feeling of being prepared to the death (that is emotional awareness) (Hebert et al, 2006). As a consequence of this difference, this emotional preparedness is not only depending on medical information.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have hypothesized that open and frequent communication between FCGs and HCPs can have a positive influence on bereavement outcomes (Herbert et al, 2006). Knowing what to expect, having someone who will listen, and strong relationships between families in palliative care and HCPs is considered important for a positive end-oflife experience (Steinhauser et al, 2000).…”
Section: Discussionmentioning
confidence: 99%